Human resources in sports a managerial approach - Tiell, Bonnie; Walton, Kelley (Burlington, Massachusetts Jones & Bartlett Learning, 2018)
"This book is written for upper-level undergraduate and graduate students pursuing a degree in Sports and Recreation Management, Sports Administration, Coaching, Physical Education, Sports Business, or similar curriculum. Although this will likely be valuable to managers and directors currently working in the sports, recreation, and fitness industry however this is not a market we will actively pursue. Throughout the chapters are examples of forms and documents used by managers and/or human resource specialists in arenas, stadiums, gymnasiums, front offices, fitness centers, golf clubs, bowling alleys, ice rinks, weight rooms, race courses, riding trails, campgrounds, and track complexes. No previous textbook has included the depth of practical applications of human resource tools and activities originating from real professionals with real experience in the field. Each chapter is organized with learning outcomes, an overview of the topic, applicable documents, a summary, key terms, discussion questions, and a global spotlight. The practicality of documented human resource applications and best practices transcends the pages of a textbook designed to engage future and current practitioners in all sectors of sports and recreation." --
Preseason planning -- Xs and Os: strategic human resource planning in sports organizations -- Roster changes: preparing for vacancies in sports organizations -- Monday morning quarterback: legal issues in human resource planning for sports organizations -- The grind: recruiting in sport organizations -- Pre-game staffing: line-ups and match ups -- Blue chippers and bench warmers: screening and selecting employees in sports organizations -- Show me the money: compensation and benefits administration in sports -- Hard knocks: negotiations, employment agreements, and labor relations -- Game time: executing a winning performance -- Practice makes perfect: training in sports organizations -- Leading the league: staff supervision and leadership -- Sport and human resources: a managerial approach -- Game changers: performance counseling & conflict resolution in sports organizations -- Post-game extras: preparation never ceases -- A must-win ballgame: diversity and inclusion in sports organizations -- Selected workplace issues in sports -- The next level: professional development and career trends in sports.
Includes bibliographical references and index
Keywords: Personnel management; Sports administration